The Role of Natural Gas in the Economic Diversity of the Kurdistan Region - Hawre Latif Majeed; Hazhar Omer Mohammed; Beston Muhammed Qadir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The use of energy sources in the world is increasing day by day, especially natural gas, and the Kurdistan Region is a naturally gas-rich region that has a rate of 5.6 trillion cubic meters, which can be a source of income and a role in economic diversity. Gas is a valuable source of electricity production and the resolution of electricity problems in the Kurdistan Region-Iraq. The study was used within the framework of the west's path to access information and research, the method of research, and the method of marketing at the local, regional and global levels. also, by marketing the natural gas of the Kurdistan Region and providing a suitable environment for investment.